Frequency-Invariant Uniform Circular Array for Wideband mm-Wave Channel Characterization - Fengchun Zhang; Wei Fan; Pedersen, Gert F. (IEEE antennas and wireless propagation letters, 2017)
A new approach for designing frequency-invariant (FI) uniform circular array (UCA) is proposed, and its application to wideband multipath estimation at millimeter-wave (mm-wave) bands is studied. Both numerical simulations and channel sounding results at mm-wave bands are provided to demonstrate the effectiveness and improvement of the proposed method in channel parameter estimation over the conventional FI UCA method.